Análisis sedimentológico y bioestratigráfico de afloramientos del Serpujoviense inferior (Mississipp - Rodríguez, Sergio; Cózar, Pedro; Mas, Ramón (Coloquios de Paleontología, 2004)
Three thick stratigraphic sections and two small outcops have been studied in Mississippian rocks to NW Adamuz. These rocks have been interpreted as slope facies, containing a hemipelagic background sedimentation, with common olistolites, debris flows, slumps and turbidite beds. The majority of the olistolites and clasts embedded in the debris flows are assigned to the late Viséan, but some olistolites, turbidite beds and wackestones of sponge spicules (Iikely also background sedimentation), exhibit foraminiferal and algal assemblages assigned to the Pendleian (early Serpukhovian). Thus, the age of the entire deposit is considered as Pendleian in age. Stratigraphic, biostratigraphic and sedimentological features of this area in Adamuz are similar to those described in the literature from the Guadiato Area, which contains one of the scarce record of Pendleian carbonate rocks in the region. However, some differences have been also recognised, and thus, the correlation between the Guadiato Area and Adamuz is questionable, because the tectonic conditions which controlled the sedimentation in both areas are slight1y different.
Keywords: Stratigraphy; Biostratigraphy; Carboniferous; Sierra Morena; Spain